Filsafat ilmu dan transformasi pendidikan agama kristen di era digital - Robinhot Sihombing; Samuelson Halomoan; Masriana Silitonga; Sumingse Eunike; Josep Lumbantoruan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to examine the role of the philosophy of science as a foundation in the transformation of Christian Religious Education in the digital era. Using a qualitative research method through literature review, this study analyzes various literatures related to the philosophy of science, educational technology, and the development of Christian Religious Education in the context of digitalization. The results show that the philosophy of science is an important foundation for understanding and integrating digital technology without neglecting Christian faith values. This educational transformation brings a paradigm shift that demands the adaptation of methods and learning media to be more relevant and effective in addressing the challenges of the digital era. Furthermore, the study identifies various challenges such as digital ethics and the risk of individualism that educators and learners must face. However, the digital era also opens great opportunities for the development of innovative learning media that can enhance the quality and attractiveness of Christian Religious Education. The philosophical implications of this transformation emphasize the importance of maintaining spiritual and moral integrity in educational practice, so that the younger generation is not only intellectually intelligent but also strong in faith and character. In conclusion, the transformation of Christian Religious Education in the digital era must be based on the philosophy of science to create an adaptive education rooted in Christian values